Study on greywater usage in the mosque - Tan, Mei Shan; Utaberta, Nangkula; Mohd Yunus, Mohd Yazid; Ismail, Nor Atiah; Ismail, Sumarni; Mohd Ariffin, Noor Fazamimah (American-Eurasian Network for Scientific Information (AENSI) Publications, 2015)
Water is important as it one of the main source of living. Water has close relationship in Islamic perspectives where it has been mentioned many times in the Holy Quran. Water is not only serves for household uses but also for religious activities especially for ablution. Ablution is a ritual that has to be performed by the Muslims before the daily prayer begins and the amount of consumption is quite high. According to UNESCO, increase in population growth causes increasing in water demand which become an alarming issue to the world. Due to scarcity of water in the future, many countries have started to promote grey water reuse to ensure the availability of the resources.